Effect of Crushed Binahong (Anredera cordifolia) Leaves on Oral Health Among Pregnant Women - Adetia Pratama; Dewi Yuliana; Santi Oktavia (Genius Journal, 2026)
Introduction: Pregnancy is a common event in a woman's life. It is a physiological state accompanied by hormonal changes, which affect not only general health but also dental and oral health. A pre-survey conducted by researchers on October 14, 2025, of five pregnant women revealed that two reported using binahong leaves as a mouthwash in addition to using toothpaste to brush their teeth. Three had never used binahong as a mouthwash. Objective: The purpose of this study is the effect of boiled binahong leaves (Anredera cardifolia) on maintaining oral health in pregnant women at the Usmalanah Saddam Tanjung Senang Health Center in Bandar Lampung in 2025. Method: This research was conducted from December 18-24, 2025, at the Usmalanah Saddam Tanjung Senang Health Center in Bandar Lampung. The population consisted of 30 pregnant women. The total sampling method was used, resulting in a total sample of 30 respondents. Data collection used a salivary pH observation sheet. The statistical test used was the dependent t-test. Result Based on the data analysis, the α value was 0.000. α value <0.05. This means that boiled binahong leaves (Anredera cardifolia) have an effect on maintaining oral health in pregnant women at the Usmalanah Saddam Tanjung Senang Health Center in Bandar Lampung in 2025. Conclusion: Therefore, planting binahong leaves at home is recommended, as they are very beneficial for health, especially in maintaining personal hygiene.